A Review on overboard CEOR discharged produced water treatment and remediation - Rawindran, H. (Institute of Physics Publishing, 2017)
Produced water is a waste by-product generated during oil and gas recovery operations. It contains the mixture of organic and inorganic compounds. Produced water management is a challenge faced by the petroleum practitioners worldwide. Build-up of chemical wastes from produced water causes huge footprint, which results in high CapEx and OpEx. Different technologies are practiced by various practitioners to treat the produced waste water. However, the constituents removed by each technology and the degree of organic compound removal has to be considered to identify the potential and effective treatment technologies for offshore industrial applications. Current produced water technologies and their successful applications have advantages and disadvantages and can be ranked on the basis of several factors, such as their discharge limit into water bodies, reinjection in producing well, or for any miscellaneous beneficial use. This paper attempts to provide a review of existing physical and chemical treatment technologies used for management of produced water. Based on our analysis, suitable methods will be recommended for offshore waste water treatment technologies. © Published under licence by IOP Publishing Ltd.